Evaluation of Molecular Species of Prostate-Specific Antigen Complexed with Immunoglobulin M in Prostate Cancer and Benign Prostatic Hyperplasia - Goč, Sanja; Janković, Miroslava (Disease Markers, 2013)
This study was aimed at defining molecular species of prostate-specific antigen (PSA) in immune complexes with immunoglobulin M (IgM). Having in mind the oligoreactivity of IgM and its preference for carbohydrate antigens, there is the possibility that it can selectively recognize known PSA glycoisoforms. PSA-IgM complexes and free PSA fractions were separated from the sera of subjects with prostate cancer (PCa) and benign prostatic hyperplasia (BPH) by gel filtration and subjected to on-chip immunoaffinity and ion-exchange chromatography. PSA-immunoreactive species were detected using surface-enhanced laser desorption/ionization time of flight mass spectrometry. The obtained spectra were analyzed for protein and glycan composition. The general pattern of the molecular species of PCa PSA and BPH PSA found in complexes with IgM was similar. It comprised major peaks at 17 kDa and minor peaks at 28 kDa, corresponding to the entire mature glycosylated PSA. The main difference was the presence of incompletely glycosylated 26.8 kDa species, having putative paucimannosidic structures, observed in PCa PSA-IgM, but not in BPH PSA-IgM. Characteristic PCa PSA-IgM glycoforms pose the question of the possible role of glycosylation as a framework for immune surveillance and may be of interest in light of recent data indicating mannose-containing glycans as cancer biomarker.